Two-stage Exchange Knee Arthroplasty: Does Resistance of the Infecting Organism Influence the Outcome? - Kurd, Mark F. (Springer-Verlag, 2010)
BACKGROUND: Periprosthetic joint infection after TKA is a challenging complication. Two-stage exchange arthroplasty is the accepted standard of care, but reported failure rates are increasing. It has been suggested this is due to the increased prevalence of methicillin-resistant infections. QUESTIONS/PURPOSES: We asked the following questions: (1) What is the reinfection rate after two-stage exchange arthroplasty? (2) Which risk factors predict failure? (3) Which variables are associated with acquiring a resistant organism periprosthetic joint infection? METHODS: This was a case-control study of 102 patients with infected TKA who underwent a two-stage exchange arthroplasty. Ninety-six patients were followed for a minimum of 2 years (mean, 34.5 months; range, 24–90.1 months). Cases were defined as failures of two-stage exchange arthroplasty. RESULTS: Two-stage exchange arthroplasty was successful in controlling the infection in 70 patients (73%). Patients who failed two-stage exchange arthroplasty were 3.37 times more likely to have been originally infected with a methicillin-resistant organism. Older age, higher body mass index, and history of thyroid disease were predisposing factors to infection with a methicillin-resistant organism. CONCLUSIONS: Innovative interventions are needed to improve the effectiveness of two-stage exchange arthroplasty for TKA infection with a methicillin-resistant organism as current treatment protocols may not be adequate for control of these virulent pathogens. LEVEL OF EVIDENCE: Level IV, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.